The Images of Nations’ Locus in the Axiosphere of the Culture - Niewiara, Aleksandra (Vilnius University Open Series, 2021)
The article contains reflections on axiology of such cultural conceptualizations as images of nations and countries. The problem is presented as being of interest to imagology (a humanities discipline). Special emphasis is on the ideas of the precursor of Polish imagology, Jan Stanislaw Bystroń. The principle of “centrality” proposed by Bystroń in 1923 as having an impact on the evaluation and construction of images of nations, ethnic groups and countries, is presented as corresponding to the “me first” image scheme proposed by cognitive linguistics and confronted with the philosophical concept of ordo amoris by Max Scheller, according to which man knows and evaluates the world not only in accordance with his mind and will, but above all in accordance with the fundamental order of love. The issue was discussed on the basis of statements about Poles and Lithuanians.
Keywords: imagology; axiolinguistics; evaluation in stereotypes of nations